Assessing the Effectiveness of Tahfiz Program Integration in Enhancing Students’ Understanding of Quran and Hadith at MIS Muhammadiyah, Foa Village - Khoirul Azmi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the effectiveness of integrating the tahfiz program into the learning of Qur’an and Hadith at Madrasah Mis Muhammadiyah Desa Foa. Such integration is considered essential, as memorizing the Qur’an not only serves as an academic achievement but also provides a solid foundation for deepening the understanding of Islamic teachings. This research employed a qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the integration of tahfiz with Qur’an and Hadith learning significantly enhances students’ comprehension. This is evident from their ability to connect memorized verses with the context of the lessons, as well as from improvements in conceptual understanding and the application of Qur’anic values. Supporting factors include students’ intrinsic motivation, teacher competence, and a conducive school environment, while challenges involve heavy memorization loads and limited classroom time. The study concludes that integrating tahfiz into Qur’an and Hadith learning is an effective strategy to improve educational quality, provided that it is managed carefully to maintain a balance between memorization and comprehension.